Implementation of Empowerment Strategy Model for Urban Poor Based on Market Needs at The Public Vocational Training Center (BBPLK) Semarang - Ilyas, Ilyas; Mulyono, Sungkowo Edy; Malik, Abdul; Larasati, Namira Putri; Loretha, All Fine (Future Science / FSH-PH Publications, 2022)
During Covid 19 pandemic, poverty is tremendously raising and expanding across the country, worsened the economic sector in almost every region in Indonesia, including in Semarang, Central Java. According to the number of residents living in Semarang, 79,058 people experienced an economic weakening in 2021. Based on the problem above, it can be concluded that there is a need for a community empowerment strategy model that is appropriate to market needs. This study reveals the implementation of a strategy model for empowering the urban poor based on market needs in the non-formal education carried out by BBPLK Semarang. This study uses a qualitative approach. The subjects of the research were 5 trainees and instructors. The technique of data collection was done by interview, observation, and documentation. To test the validity of the data, this study used technical triangulation. Data were analyzed using descriptive qualitative. This process put 3 activities, namely, (1) data reduction, (2) data presentation, and (3) drawing conclusions or verification. The community empowerment model implemented at BBPLK uses a strategy model for empowering the urban poor based on market needs. The stages of community empowerment are carried out through the awareness stage, the skill transformation stage, and the intellectual and innovative ability improvement stage. A common obstacle that occurs in BBPLK Semarang is the lack of instructors. BBPLK Semarang is still not being able to hold their instructors, so they need help from other parties such as a Private vocational training center in Semarang. Moreover, the most influential factor is the intention of the training participants themselves and the people who are reluctant to follow the training at BBPLK Semarang.